-4x-39=59-9x

Simple and best practice solution for -4x-39=59-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x-39=59-9x equation:


Simplifying
-4x + -39 = 59 + -9x

Reorder the terms:
-39 + -4x = 59 + -9x

Solving
-39 + -4x = 59 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
-39 + -4x + 9x = 59 + -9x + 9x

Combine like terms: -4x + 9x = 5x
-39 + 5x = 59 + -9x + 9x

Combine like terms: -9x + 9x = 0
-39 + 5x = 59 + 0
-39 + 5x = 59

Add '39' to each side of the equation.
-39 + 39 + 5x = 59 + 39

Combine like terms: -39 + 39 = 0
0 + 5x = 59 + 39
5x = 59 + 39

Combine like terms: 59 + 39 = 98
5x = 98

Divide each side by '5'.
x = 19.6

Simplifying
x = 19.6

See similar equations:

| p=r+p | | 25m+75=30m | | x+29y=180 | | 5x+28=40-7x | | 25-x=18.6 | | 5x+3x-8=2x+16 | | 130d=2r | | 2x+(x+2)=4 | | 22-y=1 | | 30c=75 | | 29y+x=180 | | 5a+4(3a-8)=x-8x | | 10-x=-23 | | -27-11+16+67+15-31= | | -2c-10+5c-25= | | 3(-2+3x)=9x-4 | | t-2c=5 | | 5-x-2=3+4x+5x | | 16+x=21 | | Y=-0.1x-7.2 | | 5-X=-18 | | 4x-7(313x)-9= | | 3(k-2)-7=3k-(2k-1) | | -x-144=38-9x | | 0.72x-11=2.32x+21 | | -5(r-5)+7(r-1)=-78 | | 4x+20=-10 | | 7-23+15-36= | | 9.1=1.4-6.3 | | 7m+6-8m=36 | | 12v^2+23v-24=0 | | 2-x=-22 |

Equations solver categories